The story of the world : [From prehistory to the present] - Bartlett, W. B. (Stroud, Gloucestershire : Amberley Publishing, 2015)
A history of the events that have shaped our world.
Previously published in hardback in 2014.
Includes bibliographical references (pages 506-508) and index.
Keywords: Historia universal